2015
DOI: 10.1186/s12864-015-1801-0
|View full text |Cite
|
Sign up to set email alerts
|

Comparative genome analysis of Mycoplasma pneumoniae

Abstract: BackgroundMycoplasma pneumoniae is a common pathogen that causes upper and lower respiratory tract infections in people of all ages, responsible for up to 40 % of community-acquired pneumonias. It also causes a wide array of extrapulmonary infections and autoimmune phenomena. Phylogenetic studies of the organism have been generally restricted to specific genes or regions of the genome, because whole genome sequencing has been completed for only 4 strains. To better understand the physiology and pathogenicity o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
85
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 71 publications
10
85
0
Order By: Relevance
“…To demonstrate the effectiveness of the CREASPY-cloning strategy, we cloned with a high efficiency the genome of Mycoplasma pneumoniae M129 20 in yeast, while simultaneously deleting a gene encoding for a virulence factor. Analysis showed that the cloned genome was intact and essentially error-free.…”
Section: Introductionmentioning
confidence: 99%
“…To demonstrate the effectiveness of the CREASPY-cloning strategy, we cloned with a high efficiency the genome of Mycoplasma pneumoniae M129 20 in yeast, while simultaneously deleting a gene encoding for a virulence factor. Analysis showed that the cloned genome was intact and essentially error-free.…”
Section: Introductionmentioning
confidence: 99%
“…Of the entire pan-genome, the core genome represents 55% of all genes. This level of similarity between M. hominis strains is in stark contrast to M. pneumoniae where over 99% identity has been observed between the genomes [30]. Congruence of the M. hominis pan-genome to other Mycoplasma species was assessed by comparison to M. pneumoniae (strain M129) and U. parvum serovar 3 (strain AF222894, ATCC 700970).…”
Section: Discussionmentioning
confidence: 99%
“…This sequence was derived from laboratory strain M129. Since 2013, several other genomic sequences have been published (Lluch-Senar et al, 2015; Simmons et al, 2013; Xiao et al, 2015). Most of these sequences were obtained in two independent studies.…”
Section: Introductionmentioning
confidence: 99%
“…Most of these sequences were obtained in two independent studies. One of these studies reported the comparative genome analysis of 15 M. pneumoniae strains isolated form respiratory tract samples and cerebrospinal fluid samples collected from patients between 1940 and 2009 in the USA, China, and England (Xiao et al, 2015). The other study reported the sequences of 23 clinical M. pneumoniae strains isolated between 1964 and 2011 in six different countries (Lluch-Senar et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation